Original Articles. Issue 169 (12th February 2016) - Cheng, Chuanpin; Xiong, Ying; Yang, Feng; Li, Jingqi; Tang, Minghua; Li, Zheng
Abstract: By adjusting different polarization status in ferroelectric thin films, effect of saturation polarization, bias voltage, dielectric barrier width, and ferroelectric barrier width on electrical properties of a metal-dielectric-ferroelectric-metal structure are investigated in detail. Our simulation results show that the electrical properties of the tunnel junction can be effectively improved by utilizing the inverse piezoelectric effect of ferroelectric thin films. When the strain effect is taken into account, by controlling the polarization of the ferroelectric layer, the number of logic values could be modulated flexibly.